Nutritional status and prevalence of anemia in patients with Crohn’s disease after surgery: a multicenter cross-sectional study in China - Shen, Yu; Liu, Huaying; Liu, Jing; Tang, Changling; Liu, Zhijian; Dai, Xujie; Liu, Wei; Cao, Qian; Ge, Xiaolong; Zhou, Wei (Frontiers in Nutrition, 2025)
BackgroundMalnutrition and anemia are major concerns that significantly impact quality of life and disease activity in patients with Crohn’s disease (CD) following surgical resection. However, comprehensive data on nutritional status and anemia in post-surgical CD patients remain limited. This study aims to evaluate the prevalence of malnutrition and anemia in a multi-center cohort of CD patients after surgery.MethodsIn this cross-sectional study, patients with CD who underwent bowel resection across 20 provinces in China were evaluated for nutritional status and anemia. Biochemical parameters were collected and analyzed to explore their associations with nutritional status and anemia.ResultsA total of 160 patients, with a mean age of 37.6 years and 63.8% male, were enrolled. Malnutrition was observed in 47.5% of patients, with 56.3% at risk of malnutrition post-surgery. Malnourished patients exhibited lower nutritional indicators and more severe disease activity. Anemia was detected in 60.6% of patients, with 79.4% having mild anemia and 20.6% moderate anemia. Patients with post-surgical anemia showed elevated inflammatory markers and increased disease activity. Both malnutrition and anemia were significantly associated with reduced quality of life (p < 0.05).ConclusionMalnutrition and anemia were highly prevalent and negatively impacted patients with CD following surgery. Screening and early preventive management of malnutrition and anemia were critical components of postoperative care in CD.